Carbon-based wave-absorbing composite material and preparation method thereof
By combining coal hydrogenation semicoke with graphene oxide and combining dielectric loss and magnetic loss materials, a low-cost, simple process carbon-based absorbing composite material is prepared, which solves the complex preparation of existing materials and The high cost problem achieves good absorption performance and impedance matching.
Patent Information
- Application Number
- CN202411548085.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
AI Technical Summary
The preparation process of existing carbon-based absorbent materials is complex, has high cost, and is difficult to achieve impedance matching, which affects the absorption effect.
The carbon-based absorbing composite material is prepared by electrostatic self-assembly and in situ reduction method by electrostatic self-assembly and in-situ reduction.
It realizes a low-cost, simple preparation, and both electromagnetic loss mechanism, and has good absorption performance and impedance matching characteristics.
Smart Images

Figure CN119463510A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, in particular to a carbon-based wave-absorbing composite material and a preparation method thereof. Background Art
[0002] In the face of increasingly severe electromagnetic pollution and the urgent need for military stealth, it is of great significance to design high-performance absorbing materials with strong absorption, wide bandwidth, light weight, low cost, easy preparation, stable physical and chemical properties, and large-scale application. Carbon-based absorbing materials have attracted much attention due to their low density, good oxidation resistance and corrosion resistance.
[0003] Carbon materials such as graphene are good absorbers, but as fillers, they only have one loss mechanism, which is dielectric loss. When the amount added is high, it is easy to cause impedance mismatch, thus affecting the absorption effect. In addition, the preparation process of graphene is complicated, the preparation cycle is long and the price is relatively expensive (such as the Hummers method), which limits its large-scale application. Therefore, it is of great significance to develop new carbon-based absorbers with abundant sources, low prices and simple preparation processes. Coal hydrogasification semi-coke (SC) is a solid product of coal hydrogasification, with a yield of up to 40-50%. It has the characteristics of abundant sources, low prices and rich porous structures. The high added value utilization of SC has always been a hot topic of research. The use of SC as a precursor to prepare absorbent materials can make full use of its inherent structural characteristics. For example, in order to reduce the amount of graphene and reduce costs, a new absorbent was invented by compounding SC and graphene oxide. Under the condition of low total filler content of the composite absorbent, good electromagnetic wave absorption performance was achieved. In addition, the combination of dielectric loss material and magnetic loss material can give full play to the dielectric loss and magnetic loss mechanisms, thereby obtaining an absorbing material with good impedance matching characteristics. In view of the above characteristics, the present invention aims to seek a new method in which all raw materials are cheap and easy to obtain, the operation is simple, the electrical loss and magnetic loss mechanisms are combined, the amount of absorbing agent is small, and the absorbing performance is good. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a carbon-based microwave absorbing composite material and a preparation method thereof.
[0005] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0006] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0007] S1. Prepare a cobalt nitrate methanol solution of a certain concentration, add SC, perform ultrasonication, filter, and stand to obtain a mixture;
[0008] S2, preparing a 2-methylimidazole methanol solution of a certain concentration, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly magnetically stirring, standing, centrifuging, washing, and freeze-drying to obtain a precursor;
[0009] S3, annealing the precursor to obtain a composite absorber;
[0010] S4. Evenly mix the composite absorber and paraffin, and perform ultrasonic treatment to obtain a carbon-based absorbent composite material.
[0011] As a preferred embodiment of the method for preparing a carbon-based wave-absorbing composite material according to the present invention, wherein: in the step S1, the concentration of the cobalt nitrate methanol solution is 0.05-2 mol / L.
[0012] As a preferred embodiment of the method for preparing a carbon-based microwave-absorbing composite material according to the present invention, in step S1, the mass ratio of SC to cobalt nitrate is (5-10):1.
[0013] As a preferred embodiment of the method for preparing a carbon-based microwave-absorbing composite material according to the present invention, in step S2, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is (2-20):1.
[0014] As a preferred embodiment of the method for preparing a carbon-based wave-absorbing composite material according to the present invention, in step S2, the stirring time is 4 to 10 hours, and the standing time is 10 to 24 hours.
[0015] As a preferred embodiment of the method for preparing a carbon-based wave-absorbing composite material according to the present invention, in said step S2, the centrifugal speed is 2000-8000 rpm, and the centrifugal time is 15-40 min.
[0016] As a preferred embodiment of the method for preparing a carbon-based wave-absorbing composite material according to the present invention, in step S3, the annealing temperature is 600-900° C., and the annealing time is 1-4 hours.
[0017] As a preferred embodiment of the method for preparing a carbon-based microwave-absorbing composite material according to the present invention, in step S3, annealing is performed under a nitrogen atmosphere.
[0018] As a preferred embodiment of the method for preparing a carbon-based microwave-absorbing composite material according to the present invention, in said step S4, the content of the composite microwave-absorbing agent in the carbon-based microwave-absorbing composite material is 20-50 wt%.
[0019] As a preferred embodiment of the method for preparing a carbon-based wave-absorbing composite material according to the present invention, in step S4, the water temperature for ultrasonic treatment is 70-80° C., and the ultrasonic treatment time is 5-10 min.
[0020] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0021] A carbon-based wave-absorbing composite material is prepared by the above-mentioned preparation method.
[0022] As a preferred embodiment of the carbon-based absorbing composite material described in the present invention, when the thickness of the carbon-based absorbing composite material is 1.5 to 5.0 mm, it has a minimum reflection loss of -10 to -50 dB and an absorption bandwidth of 1 to 7 GHz.
[0023] As a preferred embodiment of the carbon-based absorbing composite material described in the present invention, when the heat treatment temperature is 700°C and the mass fraction of the absorber is 30%, the carbon-based absorbing composite material has a minimum reflection loss of -33.05dB at a frequency of 9.2GHz when the thickness is 2.5mm, and the effective absorption bandwidth is 5.0GHz at 1.6mm.
[0024] The beneficial effects of the present invention are as follows:
[0025] The present invention proposes a carbon-based wave-absorbing composite material and a preparation method thereof. On the one hand, the characteristics of SC raw materials being cheap and readily available, porous structure, graphitization characteristics and inherent magnetism are utilized. On the other hand, the characteristics of cobalt-based imidazolate skeleton materials being cheap and readily available, and easy to operate are utilized. The two are composited to prepare wave-absorbing agents through electrostatic self-assembly and in-situ reduction methods, and a series of novel carbon-based wave-absorbing materials loaded with cobalt nanoparticles are obtained. The present invention makes full use of the characteristics of hydrogenated gasified semi-coke porous structure and a small amount of oxygen-containing functional groups, and uniformly grows the cobalt-based imidazolate skeleton (ZIF-67) on the pores and pore walls of SC, so that the composite material has good wave-absorbing performance. In addition, the raw materials required for the preparation of the composite material are cheap and readily available, and the preparation process is also very simple. The invention provides a convenient, efficient, green and sustainable new way for the reuse of SC. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 This is a SEM image of the composite absorber prepared in Example 1 of the present invention;
[0028] Figure 2 The hysteresis loop of the composite absorber and SC prepared in Example 1 of the present invention;
[0029] Figure 3 The real part of the dielectric constant of the carbon-based microwave absorbing composite material and SC prepared in Example 1 of the present invention;
[0030] Figure 4 The microwave absorbing performance of the carbon-based microwave absorbing composite material prepared in Example 1 of the present invention.
[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0032] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention uses SC as a carbon precursor, fully utilizes the characteristics of SC's porous structure, and uses two cheap raw materials, 2-methylimidazole and cobalt nitrate, to introduce magnetic components into SC, thereby substantially improving the wave absorption performance of the composite material. It has the following advantages:
[0034] (1) All raw materials are readily available and low in cost;
[0035] (2) The reaction conditions are mild and the operation is simple;
[0036] (3) After introducing a small amount of cobalt-based imidazole ester framework material, the microwave absorption performance was greatly improved compared with the materials after annealing SC and ZIF-67 separately, indicating that the combination of the two has greatly improved the microwave attenuation ability and the impedance matching effect;
[0037] (4) The inherent porosity and small amount of oxygen-containing functional groups of SC are conducive to the growth of cobalt-based imidazolate skeleton materials on the pore walls and inside the pores. Therefore, after annealing, not only magnetic cobalt particles and more abundant pores are introduced into SC, but the cobalt-based imidazolate skeleton material itself is also reduced and introduced into micropores and graphitized carbon. Therefore, the composite material can give full play to the synergistic mechanism of multi-level reflection and scattering, magnetic loss, interface polarization and dipole polarization loss.
[0038] (5) The total filler content is 20 to 50 wt%, which is lower than most existing carbon-based absorbing composite materials. When the thickness is 1.5 to 5.0 mm, the minimum reflection loss is -10 to -50 dB, and the absorption bandwidth is 1 to 7 GHz, thus obtaining a composite material with good absorbing performance.
[0039] According to one aspect of the present invention, the present invention provides the following technical solution:
[0040] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0041] S1. Prepare a cobalt nitrate methanol solution of a certain concentration, add SC, perform ultrasonication, filter, and stand to obtain a mixture;
[0042] S2, preparing a 2-methylimidazole methanol solution of a certain concentration, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly magnetically stirring, standing, centrifuging, washing, and freeze-drying to obtain a precursor;
[0043] S3, annealing the precursor to obtain a composite absorber;
[0044] S4. Evenly mix the composite absorber and paraffin, and perform ultrasonic treatment to obtain a carbon-based absorbent composite material.
[0045] Preferably, in step S1, the concentration of the cobalt nitrate methanol solution is 0.05-2 mol / L. The concentration of the cobalt nitrate methanol solution should be moderate. If the concentration is too high, the metal organic framework particles will become larger and easily agglomerated when reacting with 2-methylimidazole in the later stage; if the concentration is too low, the reaction rate will decrease, the reaction time will be prolonged, and the efficiency will be reduced.
[0046] Preferably, in step S1, the mass ratio of SC to cobalt nitrate is (5-10): 1. When the present invention exerts its absorbing effect, dielectric loss is the main loss mechanism, so the mass of SC is relatively large. In addition, magnetic cobalt particles will exert magnetic loss to enhance the impedance matching of the material, but the density of cobalt is relatively high. When the content is high, the density of the composite material will increase, which is contrary to the original intention of the lightweight absorbing material. Therefore, a suitable initial ratio of the two is crucial to improving the absorbing performance.
[0047] Preferably, in step S2, the molar ratio of 2-methylimidazole to cobalt nitrate is (2-20):1. 2-methylimidazole reacts with cobalt nitrate to form a typical ZIF-67, which is self-assembled by coordinated Co ions and imidazole. Therefore, the morphology of ZIF-67 and the size of nanoparticles depend on the molar ratio of the two. If the 2-methylimidazole content is low, more products with non-rhombic dodecahedral structures will be generated. A moderate ratio of 2-methylimidazole content will obtain a perfect dodecahedral structure of ZIF-67, and the nanoparticles are small and uniform in size. In addition to increasing the cost, an excessively high 2-methylimidazole content no longer plays a leading role in controlling the material morphology and size.
[0048] Preferably, in step S2, the stirring time is 4 to 10 hours and the standing time is 10 to 24 hours. During the stirring process, the N atom on the 2-methylimidazole ring provides unpaired electrons to react with the Co in the cobalt salt. 2+Forming coordination bonds. Because of the presence of SC, sufficient stirring time is required to allow ZIF-67 to grow evenly inside the pores of the semi-coke. Otherwise, SC cannot be dissolved in methanol and sinks to the bottom of the beaker, and most of the ZIF-67 in the product will be free in methanol. After sufficient stirring to allow ZIF-67 to grow inside the pores of the semi-coke, it is crucial to allow the crystals to grow further after standing.
[0049] Preferably, in step S2, the centrifugal speed is 2000-8000 rpm, and the centrifugal time is 15-40 min. Because the density of SC grown with ZIF-67 is still low, the centrifugal speed below 2000 rpm cannot achieve the purpose of separation. The length of the centrifugal time depends on the selected centrifugal speed and the amount of centrifugation required. Generally, the higher the centrifugal speed, the shorter the centrifugal time, and each centrifugal time should not be less than 15 min.
[0050] Preferably, in step S3, the annealing temperature is 600-900°C, the annealing time is 1-4 hours, and the annealing treatment is performed in a nitrogen atmosphere. The annealing temperature should be in a suitable range. If the annealing temperature is lower than 600°C, the degree of in-situ reduction of the composite material is low, while if the annealing temperature is higher than 900°C, the energy consumption is increased, the degree of reduction is too high, the conductivity is too high, and the wave absorption performance is reduced.
[0051] Preferably, in step S4, the content of the composite absorber in the carbon-based absorbent composite material is 20-50wt%. The appropriate ratio of the composite absorber to paraffin wax enables the composite material to have a moderate dielectric constant and magnetic permeability, and enables the composite material to have good impedance matching characteristics and a high attenuation constant, which is conducive to improving the absorbent performance.
[0052] Preferably, in step S4, the water temperature for ultrasonic treatment is 70-80°C, and the ultrasonic treatment time is 5-10 minutes. Because the melting point of paraffin is 57-63°C, the water temperature for ultrasonic treatment should be higher than its melting point, but not too high, otherwise the ultrasonic process will easily cause the glass container to burst, increasing safety hazards. The ultrasonic time should be appropriate. Ultrasonic treatment at a temperature of 70-80°C for more than 10 minutes will easily cause the decomposition of certain components in the absorber, which is not conducive to the stability of the system.
[0053] According to another aspect of the present invention, the present invention provides the following technical solution:
[0054] A carbon-based wave-absorbing composite material is prepared by the above-mentioned preparation method.
[0055] Preferably, when the thickness of the carbon-based absorbing composite material is 1.5 to 5.0 mm, it has a minimum reflection loss of -10 to -50 dB and an absorption bandwidth of 1 to 7 GHz. Further preferably, when the heat treatment temperature is 700°C and the mass fraction of the absorber is 30%, the carbon-based absorbing composite material has a minimum reflection loss of -33.05 dB at a frequency of 9.2 GHz when the thickness is 2.5 mm, and the effective absorption bandwidth is 5.0 GHz at 1.6 mm.
[0056] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0057] Performance tests in various embodiments and comparative examples:
[0058] (1) Surface morphology analysis
[0059] The surface morphology of the absorber was measured by a field emission scanning electron microscope JSM-7001.
[0060] (2) X-ray diffraction analysis
[0061] The crystal structure image of the sample was measured by Bruker Advance D8.
[0062] (3) Hysteresis loop test
[0063] The magnetic properties of the samples were measured by a hysteresis loop analyzer (LakeShore 7404).
[0064] (4) Microwave vector network analysis test
[0065] Sample preparation method: The composite material is made into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm, and then the electromagnetic parameters of the sample are measured by the coaxial transmission / reflection method. The electromagnetic parameters of the sample are measured by a microwave vector network analyzer VNAE5071C. The reflection loss (RL), attenuation constant and impedance matching are obtained by electromagnetic parameter calculation.
[0066] Example 1
[0067] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0068] S1, prepare 0.1 mol / L cobalt nitrate methanol solution, add measured SC, wherein the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, filter to allow the cobalt nitrate to fully enter the pores of SC, and let stand overnight to obtain a mixture;
[0069] S2, prepare 0.1 mol / L 2-methylimidazole methanol solution, quickly pour the 2-methylimidazole methanol solution into the mixture of S1, quickly stir magnetically to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 16:1, continue stirring for 4 hours, let stand for 24 hours, centrifuge at 5000 rpm for 30 minutes, wash three times with alcohol, and freeze-dry to obtain a precursor;
[0070] S3, the precursor is loaded into a tube furnace, the heating rate is controlled to be 5°C / min, and annealed at 700°C for 2h in a nitrogen atmosphere to obtain a composite absorber, the SEM image of which is shown in Figure 1 As shown in Figure 2, it can be seen that ZIF-67 has been successfully synthesized, presenting a dodecahedral structure with a smooth and regular surface, and growing relatively evenly on the pore walls and inside the pores of SC; its hysteresis loop with SC is shown in Figure 2 Figure 2 As shown in the figure, it can be seen that SC has a certain degree of magnetism, but the magnetism is low. After the introduction of ZIF-67, the magnetism of the composite material has been greatly improved, and the saturation magnetization of SC / Co-700 has increased to 3.1emu / g. The high saturation magnetization means that the material has a stronger magnetization ability in the alternating electric field, which is conducive to magnetic loss and the improvement of wave absorption performance.
[0071] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 30%, ultrasonically treat in hot water at 70°C for 5 minutes, press into shape with a mold, and test the absorbing performance.
[0072] The real part of the dielectric constant of the carbon-based microwave absorbing composite material prepared in this embodiment is as follows: Figure 3 As shown in the figure, it can be seen that the dielectric constant of SC is very low, about 3.0, but when ZIF-67 is introduced into it and the addition amount is 30% after annealing at 700℃, the dielectric constant is greatly improved from 3.0 to 14.0. Figure 4 As shown, the reflection loss value of the material is calculated from the dielectric constant and permeability according to the transmission line theory:
[0073]
[0074] Among them, ε r and μ r are the relative permittivity and magnetic permeability. ε' and μ', ε" and μ" are the real and imaginary parts of the permittivity and magnetic permeability, respectively. in and Z 0 The input impedance of the absorber and the impedance of free space. c is the speed of light, d is the thickness, and f is the frequency. RL<-10dB means that 90% of the electromagnetic waves are absorbed by the absorber. The frequency width of RL<-10dB is called the effective absorption bandwidth. The lower the RL value, the wider the effective absorption bandwidth and the better the absorption ability. Figure 4It can be seen that the composite material of this embodiment has a minimum reflection loss of -33.05 dB at a frequency of 9.2 GHz when the thickness is 2.5 mm, and an effective absorption bandwidth of 5.0 GHz when the thickness is 1.6 mm.
[0075] Example 2
[0076] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0077] S1, prepare a 2 mol / L cobalt nitrate methanol solution, add a measured amount of SC, wherein the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, filter to allow the cobalt nitrate to fully enter the pores of SC, and let stand overnight to obtain a mixture;
[0078] S2, preparing 0.05 mol / L 2-methylimidazole methanol solution, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, quickly magnetically stirring to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 12:1, stirring continuously for 4 hours, standing for 24 hours, centrifuging at 6000 rpm for 25 minutes, washing with alcohol three times, and freeze-drying to obtain a precursor;
[0079] S3, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 700°C for 2h in a nitrogen atmosphere to obtain a composite absorber;
[0080] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 40%, ultrasonically treat it in hot water at 70°C for 5 minutes, press it into a mold, and test its absorbing performance.
[0081] The carbon-based absorbing composite material prepared in this embodiment has a minimum reflection loss of -23.05 dB at a frequency of 12.7 GHz when the thickness is 1.5 mm, and an effective absorption bandwidth of 4.1 GHz.
[0082] Example 3
[0083] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0084] S1, prepare 0.1 mol / L cobalt nitrate methanol solution, add measured SC, where the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, and filter to allow the cobalt nitrate to fully enter the pores of SC.
[0085] The mixture was allowed to stand overnight;
[0086] S2, preparing 0.1 mol / L 2-methylimidazole methanol solution, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly stirring with magnetic stirring to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 8:1, stirring continuously for 4 hours, standing for 24 hours, centrifuging at 5000 rpm for 20 minutes, washing with alcohol three times, and freeze-drying to obtain a precursor;
[0087] S3, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 800°C for 2h in a nitrogen atmosphere to obtain a composite absorber;
[0088] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 30%, ultrasonically treat in hot water at 70°C for 5 minutes, press into shape with a mold, and test the absorbing performance.
[0089] The carbon-based absorbing composite material prepared in this embodiment has a minimum reflection loss of -40.38 dB at a frequency of 12.5 GHz when the thickness is 2.0 mm.
[0090] Example 4
[0091] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0092] S1, prepare 0.15 mol / L cobalt nitrate methanol solution, add measured SC, where the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, and filter to allow the cobalt nitrate to fully enter the pores of SC.
[0093] The mixture was allowed to stand overnight;
[0094] S2, preparing 0.15 mol / L 2-methylimidazole methanol solution, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly stirring with magnetic stirring to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 16:1, stirring continuously for 6 hours, standing for 24 hours, centrifuging at 5000 rpm for 30 minutes, washing with alcohol three times, and freeze-drying to obtain a precursor;
[0095] S3, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 900°C for 2h in a nitrogen atmosphere to obtain a composite absorber;
[0096] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 25%, ultrasonically treat in hot water at 70°C for 5 minutes, press into shape with a mold, and test the absorbing performance.
[0097] The carbon-based absorbing composite material prepared in this embodiment has a minimum reflection loss of -29.17 dB when the thickness is 5.0 mm, and multi-peak absorption occurs at ~5 GHz and ~16 GHz.
[0098] Example 5
[0099] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0100] S1, prepare 0.2 mol / L cobalt nitrate methanol solution, add measured SC, where the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, and filter to allow the cobalt nitrate to fully enter the pores of SC.
[0101] The mixture was allowed to stand overnight;
[0102] S2, preparing 0.2 mol / L 2-methylimidazole methanol solution, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly stirring with magnetic stirring to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 20:1, stirring continuously for 6 hours, standing for 24 hours, centrifuging at 4000 rpm for 40 minutes, washing with alcohol three times, and freeze-drying to obtain a precursor;
[0103] S3, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 900°C for 2h in a nitrogen atmosphere to obtain a composite absorber;
[0104] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 30%, ultrasonically treat in hot water at 70°C for 5 minutes, press into shape with a mold, and test the absorbing performance.
[0105] The carbon-based absorbing composite material prepared in this embodiment has a minimum reflection loss of -32.12 dB when the thickness is 2.0 mm, and the absorption bandwidth reaches 4.5 GHz.
[0106] Comparative Example 1
[0107] A method for preparing a wave absorbing material comprises the following steps:
[0108] S1, SC was directly placed in a tube furnace, the heating rate was 5 °C / min, and annealed at 700 °C for 2 h in a nitrogen atmosphere to obtain a precursor;
[0109] S2, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 700°C for 2h in a nitrogen atmosphere to obtain a wave absorber;
[0110] S3, melt the paraffin in a drying oven at 80°C; add the absorbent to the melted paraffin, the mass fraction of the absorbent is 40%, ultrasonically treat in hot water at 70°C for 5 minutes, press into shape with a mold, and test the absorbing performance.
[0111] The absorber in this comparative example treated with SC alone has a minimum reflection loss higher than -10 dB in the tested thickness range of 1.5-5.0 mm. Its absorption performance cannot be compared with any of the above-mentioned embodiments, indicating that the introduction of magnetic cobalt is crucial to improving the absorption performance.
[0112] Comparative Example 2
[0113] A method for preparing a carbon-based microwave-absorbing composite material comprises the following steps:
[0114] S1, preparing 0.1 mol / L cobalt nitrate methanol solution and 0.1 mol / L 2-methylimidazole methanol solution, quickly pouring the 2-methylimidazole methanol solution into the cobalt nitrate methanol solution and magnetically stirring, rapidly magnetically stirring to ensure that the molar ratio of 2-methylimidazole to cobalt nitrate is 8:1, stirring continuously for 6 hours, standing for 24 hours, centrifuging at 6000 rpm for 20 minutes, washing with alcohol three times, and freeze-drying to obtain a precursor;
[0115] S2, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 700°C for 2h in a nitrogen atmosphere to obtain a composite absorber;
[0116] S4, melt the paraffin in a drying oven at 80°C; add the composite absorber to the melted paraffin, the mass fraction of the absorber is 50%, ultrasonically treat it in hot water at 70°C for 5 minutes, press it into a mold, and test its absorbing performance.
[0117] The carbon-based absorbing composite material prepared in this comparative example has a minimum reflection loss of only -19.96 dB when the thickness is 2.0 mm, and the absorbing agent content is higher than that of the above examples, but the absorption performance is much lower than that of the above examples.
[0118] Comparative Example 3
[0119] A method for preparing a wave absorbing material comprises the following steps:
[0120] S1, prepare 0.2 mol / L cobalt nitrate methanol solution, add measured SC, where the mass ratio of SC to cobalt nitrate is 5:1, ultrasonicate for 10 min, and filter to allow the cobalt nitrate to fully enter the pores of SC.
[0121] The mixture was allowed to stand overnight;
[0122] S2, subjecting the mixture of step S1 to magnetic stirring, heating to evaporate the solvent, and drying at 80° C. to obtain a precursor;
[0123] S3, loading the precursor into a tube furnace, controlling the heating rate to be 5°C / min, and annealing at 700°C for 2h in a nitrogen atmosphere to obtain a wave absorbing agent;
[0124] S4, melt the paraffin in a drying oven at 80°C; add the absorbent to the melted paraffin, the mass fraction of the absorbent is 40%, ultrasonically treat it in hot water at 70°C for 5 minutes, press it into a mold, and test the absorbing performance.
[0125] The absorbing material prepared in this comparative example has a minimum reflection loss of -24.13dB when the thickness is 2.0mm, and an absorption bandwidth of 3.2GHz. Its absorption performance is much lower than that of Example 1. The mass fraction of the absorber in Example 1 is 30%, which is lower than 40% in Comparative Example 1. The minimum reflection loss of Example 1 reaches -33.05dB, which is also better than -24.13dB in Comparative Example 1.
[0126] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a carbon-based microwave absorbing composite material, characterized in that: The steps include: S1. Prepare a cobalt nitrate methanol solution of a certain concentration, add SC, perform ultrasonication, filter, and stand to obtain a mixture; S2, preparing a 2-methylimidazole methanol solution of a certain concentration, quickly pouring the 2-methylimidazole methanol solution into the mixture obtained in step S1, rapidly magnetically stirring, standing, centrifuging, washing, and freeze-drying to obtain a precursor; S3, annealing the precursor to obtain a composite absorber; S4. Evenly mix the composite absorber and paraffin, and perform ultrasonic treatment to obtain a carbon-based absorbent composite material.
2. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In the step S1, the concentration of the cobalt nitrate methanol solution is 0.05-2 mol / L.
3. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In the step S1, the mass ratio of SC to cobalt nitrate is (5-10):
1.
4. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In the step S2, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is (2-20):
1.
5. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In step S2, the stirring time is 4 to 10 hours, and the standing time is 10 to 24 hours.
6. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In step S2, the centrifugal speed is 2000-8000 rpm, and the centrifugal time is 15-40 min.
7. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In the step S3, the annealing temperature is 600-900° C., and the annealing time is 1-4 hours; the annealing treatment is performed in a nitrogen atmosphere.
8. The method for preparing the carbon-based microwave absorbing composite material according to claim 1, characterized in that: In the step S4, the content of the composite absorber in the carbon-based absorbent composite material is 20-50 wt %; the water temperature for ultrasonic treatment is 70-80° C., and the ultrasonic treatment time is 5-10 min.
9. A carbon-based microwave absorbing composite material, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. The carbon-based microwave absorbing composite material according to claim 9, characterized in that: When the thickness of the carbon-based absorbing composite material is 1.5 to 5.0 mm, it has a minimum reflection loss of -10 to -50 dB and an absorption bandwidth of 1 to 7 GHz.